Vitamins А, С and D — Essential Trio for Infants - Evgenia V. Shikh; Anna A. Makhova; Ekaterina I. Alekseeva (Вопросы современной педиатрии)
Administration of essential vitamins A, C and D in vitamin-mineral complex in common dosage is efficient for immunity formation, harmonious physical and neuropsychic development, rickets prevention. Dosage of components at the physiological daily maintenance in basic vitamin complexes for infants is integral for nursing mother supplementation and fortification of the food used for infant weaning. If necessary, and specifically in immature infants, the basic vitamin complex (vitamins A, C and D) can be extended with other required micronutrients (vitamin D, for example, can be extended up to 1000 ME). It depends on feeding type, intake of vitamin-mineral complexes for nursing mothers, seasonal prevalence, region and many other factors.